Inhibition of MicroRNA miR-101-3p on prostate cancer progression by regulating Cullin 4B (CUL4B) and PI3K/AKT/mTOR signaling pathways. Issue 1 (1st January 2021) - Gu, Zhenhua; You, Zhixin; Yang, Yucheng; Ding, Rui; Wang, Meili; Pu, Jianming; Chen, Jian
ABSTRACT: To probe into the efffects of miR-101-3p via regulating CUL4B within PI3K/AKT/mTOR signaling pathway on progression of prostate cancer (PCA). Western blot and qRT-PCR were adopted to detect CUL4B and miR-101-3p expressions in 75 cases with PCA . The cellular strains of PCA (LNCaP and PC3) were chose as the objects to check the targeting correlation between CUL4B and miR-101-3p through dual-luciferase reporter experiments. LNCaP cells and PC3 cells were randomly divided into the blank group, miR-101-3p mimic group, siRNA negative control (NC) group, CUL4B siRNA group and CUL4B siRNA plus the miR-101-3p inhibitor group. Cellular bioactivity measurement was done via Cell-Light EDU, MTT, Annexin-V-FITC/PI, scratch-heal experiments and invasion tests of Transwell. MiR-101-3p expression was decreased more signally in tumor tissues than in normal tissues adjacent to the cancer. MiR-101-3p inhibited cellular proliferating, migrating and invasion. Nevertheless, it promoted cellular apoptosis, up-regulated apoptotic proteins as well as down-regulated anti-apoptotic proteins. CUL4B siRNA and miR-101-3p simulation were similar in terms of their outcomes. Nonetheless, these results could be reversed through the miR-101-3p inhibitor. Besides, CUL4B siRNA and the simulation halted a serious of PI3K signal in PCA cells. MiR-101-3p expression was down-regulated in PCA patients. CUL4B was upregulated in PCA patients. Moreover, miR-101-3p suppressed cellular invasion, migration, proliferation and led to cellular apoptosis, which might be related to the PI3K/AKT/mTOR signaling pathway suppression. Finally, we found, MiR-101-3P suppressed PCA progression via aiming for CUL4B, which may offer the new molecular target for PCA clinical treatment. Graphical abstract: uf0001